2022
DOI: 10.14283/jpad.2022.85
|View full text |Cite
|
Sign up to set email alerts
|

Blood Biomarkers from Research Use to Clinical Practice: What Must Be Done? A Report from the EU/US CTAD Task Force

Abstract: Timely and accurate diagnosis of Alzheimer’s disease (AD) in clinical practice remains challenging. PET and CSF biomarkers are the most widely used biomarkers to aid diagnosis in clinical research but present limitations for clinical practice (i.e., cost, accessibility). Emerging blood-based markers have the potential to be accurate, cost-effective, and easily accessible for widespread clinical use, and could facilitate timely diagnosis. The EU/US CTAD Task Force met in May 2022 in a virtual meeting to discuss… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
60
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 47 publications
(63 citation statements)
references
References 51 publications
3
60
0
Order By: Relevance
“…11 In addition, recent recommendations by the EU/US CTAD Task Force on the topic of what must be done to progress blood biomarkers from research use to clinical practice for the purpose of timely and accurate AD diagnosis, further support the use of combined biomarkers and risk factors in prediction models to limit misdiagnoses by healthcare providers. 24 In the present study, an exploratory analysis in healthy individuals indicated APS CLIA cutoff values established in cognitively impaired individuals continue to perform with high diagnostic accuracy in other populations including those who are cognitively unimpaired. Further studies in healthy individuals are currently underway to establish and expand the PrecivityAD test's diagnostic performance.…”
Section: Discussionmentioning
confidence: 65%
See 3 more Smart Citations
“…11 In addition, recent recommendations by the EU/US CTAD Task Force on the topic of what must be done to progress blood biomarkers from research use to clinical practice for the purpose of timely and accurate AD diagnosis, further support the use of combined biomarkers and risk factors in prediction models to limit misdiagnoses by healthcare providers. 24 In the present study, an exploratory analysis in healthy individuals indicated APS CLIA cutoff values established in cognitively impaired individuals continue to perform with high diagnostic accuracy in other populations including those who are cognitively unimpaired. Further studies in healthy individuals are currently underway to establish and expand the PrecivityAD test's diagnostic performance.…”
Section: Discussionmentioning
confidence: 65%
“…Similar improvements to amyloid prediction by the addition of ApoE proteotype status and age were observed in the CLIA validation studies of the PrecivityAD test and APS model used in current clinical care 11 . In addition, recent recommendations by the EU/US CTAD Task Force on the topic of what must be done to progress blood biomarkers from research use to clinical practice for the purpose of timely and accurate AD diagnosis, further support the use of combined biomarkers and risk factors in prediction models to limit misdiagnoses by healthcare providers 24 …”
Section: Discussionmentioning
confidence: 96%
See 2 more Smart Citations
“…Seed amplification assays for alpha synuclein in cerebrospinal fluid (CSF), skin, and other biofluids and mucosa offer promising avenues to overcome these disparities by relying on biological evidence over clinical assessment, especially through routes that are less invasive ( Bellomo et al, 2022 ). Similarly, more widespread use of PET and CSF measures of amyloid and tau, and, even more importantly, plasma measures of amyloid, tau, and other markers (e.g., NfL, GFAP) ( Angioni et al, 2022 ) will offer more accurate assessment of AD co-pathology. At the same, more studies need to be done to assess how clinical syndromes may differ across demographic variables and how these variables impact LBD and AD biomarkers assessments, specifically with an examination of social determinants of health ( Majoka and Schimming, 2021 ; Gleason et al, 2022 ).…”
Section: Discussionmentioning
confidence: 99%